Cosmic Ray Propagation in Galaxy Clusters and the Production of Gamma Rays and Neutrinos - Hussain, Saqib (2022)
The origin of ultra-high-energy cosmic-rays (UHECRs), diffuse neutrino, and gamma-ray background is among the major mysteries in astrophysics. The diffuse gamma-ray background (DGRB) corresponds to the one that remains after subtracting all individual sources from observed gamma-ray sky. The DGRB provides a non-thermal perspective of the universe that is also explored through the extragalactic UHECRs and neutrinos. The observed energy fluxes of these three components are all comparable suggesting that they may have a common origin.Several types of astrophysical sources have been predicted as the contributors to high-energy multi-messengers. They possibly have contributions from different source populations such as star-forming galaxies (SFGs), pulsars, active galactic nuclei (AGNs), gamma-ray bursts (GRBs), and from galaxy clusters. In particular, clusters of galaxies can potentially produce cosmic rays (CRs) up to very-high energies via large-scale shocks and turbulent acceleration. Due to their unique magnetic-field configuration and large size, CRs with energy < 1017 eV can be trapped within these structures over cosmological time scales, and generate secondary particles, including neutrinos and gamma rays, through interactions with the background gas and photon fields. In this Thesis, we combined three-dimensional (3D) cosmological MHD simulations of clusters of galaxies with the propagation of CRs using Monte Carlo simulations, considering redshifts z < 5, and computed the contribution of clusters to the diffuse background of neutrinos and gamma-rays. We used the distribution of clusters within this cosmological volume to extract their properties, including mass, magnetic field, temperature, and density. We propagated CRs in this environment considering all relevant photohadronic, photonuclear, and hadronuclear interaction processes. We have found that for CRs injected with a fraction ~ (0.5- 3)% of the clusters luminosity, spectral power law indices = 1.5 - 2.7 and cutoff energy Emax= (1016 - 1017.5) eV, the clusters contribute to a sizeable fraction of the diffuse flux of neutrinos observed by the IceCube, but most of the contribution comes from clusters with M > 1014 Msun and redshift z < 0.3. This contribution is even higher when we include the cosmological evolution of the CR sources, namely, AGNs and star-forming regions. Similarly, for the integrated diffuse gamma-ray flux, we have found that the clusters can contribute to up to 100% of the diffuse gamma-ray flux observed by the Fermi-LAT above 100 GeV, for CR injection power corresponding to ~ 1% of the clusters luminosity, spectral indices =1.5 - 2.5 and energy cutoff Emax = (1016 1017) eV. The flux is dominated by clusters with mass 1013< M/Msun < 1015 in the redshift range z < 0.3. Our results also predict the potential observation of high-energy gamma rays from clusters by experiments like HAWC, LHAASO and even the upcoming CTA.